Student perspective on entrepreneurship in social solidarity economy: an exploration at the Tecnológico de Costa Rica - Arzadun, Paula; Picado Arroyo, Rytha (Cooperativismo & Desarrollo, 2023)
The present work studies the student perspective on entrepreneurship in the field of social solidarity economy (SSE), at the Tecnológico de Costa Rica. In the country there is a varied offer of higher education institutions, among which are the five public universities, which cover the national territory with their academic training, through their different campuses and headquarters. Each of these universities is part of the National Council of Rectors (CONARE), an entity aimed at articulating the higher education system for development and links with Costa Rican society. The Tecnológico de Costa Rica (TEC) is one of these five universities, oriented especially to science and technology careers and a pioneer in topics of entrepreneurship promotion and business incubation processes, since 1994; Despite which the approach to and work with organizations in the field of SSE are not systematic. Given the gaps detected, these aspects were studied exploratoryly with a mixed approach. The results support the postulate about lack of knowledge regarding SSE as well as its absence in study programs and other university activities. The work is revealing, allowing us to glimpse future lines of action both within the TEC and in terms of interrelationships with local and international actors.
Keywords: entrepreneurship; social solidarity economy; students; university; Costa Rica